Creative memories : - Lightle, Cheryl (McGraw-Hill, 2004)
How did an unemployed single mother turn a simple business idea into a 450 million-dollar multi-national corporation? She followed her instincts, formed a strategy, and found a way to transform a vision into a home-grown direct-selling empire called Creative Memories. This astonishing self-made success story is a prime example of entrepreneurship at its best. Now the co-founder of Creative Memories shows today’s business leaders how to recognize growth opportunities, turn passions into profits, and reach even higher levels of personal and profession success.